(untitled) (Academia Journal of Medicine, 2020)
Background: Obesity is a common metabolic disease world-wide and dyslipidemias among the most common metabolic disorders associated with obesity. The present study was undertaken to assess lipid profile level among healthy subjects and their relation with obesity. Subjects and Methods: This cross sectional study was conducted on 100 subjects. General information related to data such as name, age, gender etc. was recorded in case history proforma. BMI was evaluated based on formula of BMI = Weight (kg)/Height (m)2. Based on BMI, subjects were divided into two groups according to their BMI values as- group I- Obese and Group II- Non obese. Group I had 65 and group II had 35 subjects. Lipid profile was done. Results: There was significant difference in group I and group II regarding waist circumference (WC), BMI (kg/m2), body adiposity index (BAI), visceral adiposity index (VAI), total cholesterol (TC) (P< 0.05). Waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), HDL- C, LDL- C, TG, TC/HDL- C, LDL-C/HDL-C and TG/HDL-C was non- significant (P< 0.05). There was negative correlations between BMI and TC, LDL-C, HDL-C; WC, WHR, VAI and HDL-C and positive significant correlations were found between WC, WHR, and TG/HDL-C, as well as between VAI and TC, TG, TC/HDL-C, LDL/HDL-C, and TG/ HDL-C. Conclusion: Authors found that there was alteration of lipid profile in obese subjects. VAI is strongly related with lipid profile and may be considered as reliable obesity index in obese patients with dyslipidemias.